Supply Chain Management Planning for a Project Using the Fuzzy Logic and Crasing Program Method - Elis Hertini; Julita Nahar (International Journal of Supply Chain Management, 2020)
Project management is a strategy that needs to be done in project planning and scheduling. With the preparation of a good project management, it can be estimated the time and cost needed to run the project, so as to minimize cost losses due to possible project lags. Project scheduling is one element of planning results, which can provide information about project schedules, plans and progress. Project time management can be arranged using the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT). One alternative to accelerate project completion (Crashing) is by adding project costs using the Crasing Program Method. To overcome the uncertainty of scheduling time and project costs in calculations Fuzzy Logic is used. From the results of using Fuzzy Logic, we estimate the time and cost needed to carry out the project, so as to minimize cost losses due to possible time delays in the project. The results of using Fuzzy Logic on CPM and PERT project schedule on a house renovation project in Ujungberung Indah Bandung housing complex, requires a longer completion time, but the probability of completion of the project is higher, the use of the Crasing Program Method results in faster project completion times and lower incremental costs.